Peran Ombudsman Republik Indonesia Perwakilan Provinsi Jawa Tengah Dalam Penanganan Maladministrasi Pelayanan Publik - Adhiningtyas, Citra; Astuti, Puji; Astrika, Lusia (Journal of Politic and Government Studies, 2015)
ABSTRACTThis research is based on the by the completion of the public reports of alleged maladministration of public services that have not been resolved by the Ombudsman Republic of Indonesia Central Java Province Representatives. In 2014 the Ombudsman Republic of Indonesia Central Java Province Representative receives 137 public reports and only 39% of that reports have been declared finished. From this background there are two fundamental problem, that is: (1) How is the role of the Ombudsman of the Republic of Indonesia Central Java Province Representatives in the handling of public services maladministration; (2) what are the factors inhibiting the performance of the Ombudsman of the Republic of Indonesia Central Java Province Representative in the handling of maladministration of public service. This research aims to describe the role the Ombudsman Republic of Indonesia Central Java Province Representative in the handling of public services maladministration and analyze factors that hampers its performance. The method used in this research is qualitative-descriptive method. The type of data used are primary and secondary data collected by observation, interviews and documentation.The results of this research showed that the representatives of the Ombudsman Republic of Indonesia Central Java province representative has not been optimal in dealing with maladministration of public service because it still focuses on the recommendation in the form of indirect clarification or only by mail according to the complexity of the report such as not complicated, complicated and very complicated. There are three obstacles in the effort ofaccomplishing its role that can be seen in terms of human resources, the complainant, and the responsiveness of agencies reported.Keywords: Ombudsman of the Republic of Indonesia Central Java Province Representative, Maladministration, Public Service.